Padi Berume sebagai Perwujudan Ketahanan Pangan di Desa Pangkal Niur Kabupaten Bangka: Pelestarian Kearifan Lokal di Tengah Terpaan Kerentanan - Harmin; Ebin; Ilham Rizki Juliansyah; Herza, Herza (Equilibrium: Jurnal Pendidikan, 2025)
This study aims to explore in depth the reasons why the majority of the Pangkal Niur Village community maintains the tradition of berume dryland rice farming amid various vulnerabilities, examine the manifestations of the reasons why the Pangkal Niur Village community maintains the tradition of dryland rice farming today, and analyze the local government's response to the vulnerabilities faced by dryland rice farmers. In this study, the researcher used a qualitative research method with a case study approach. Data were obtained through interviews, observations, and documentation, then analyzed using Pierre Bourdieu's social practice theory, which includes the concepts of habitus, capital, and arena. The results of the study show that there are several motives for the persistence of the berume tradition, including: (1) the manifestation of habitus that has become a tradition passed down from generation to generation; (2) the rationality that berume is more economical than paddy fields; (3) berume is a form of local food security; (4) the existence of mutual cooperation and togetherness values that continue to be upheld. In addition, the berume tradition is manifested in: (1) the continued use of traditional subsistence methods amid the modernization of farmers; (2) the use of berume rice in the nisab and memere/ngebaru (ngeberas baru) traditions; (3) intercropping rice fields with 1-3-year-old oil palm trees; (4) preserving forests because they are considered a source of freedom. Furthermore, the government, through the Bangka Food and Agriculture Service, has released local rice varieties and distributed fertilizers and pesticides to field farmers, although it is now more focused on paddy rice because of its higher production.